The hidden price of repeated traumatic exposure: different cognitive deficits in different first-responders - Levy-Gigi, Einat; Richter-Levin, Gal; Kéri, Szabolcs (Frontiers in Behavioral Neuroscience, 2014)
Studies on first responders who are repeatedly exposed to traumatic events report low levels of PTSD symptoms and diagnosis. However, neuroimaging and behavioral studies show that traumatic exposure is associated with brain and cognitive dysfunctions. Taking together it may suggest that traumatic exposure have a price, which is not sufficiently defined by the standard PTSD measures. In a recent study we revealed that similar to individuals with PTSD, non-PTSD highly exposed firefighters display a selective impairment in hippocampal related functions. In the current study we aimed to test whether different first responders display a similar impairment. We concentrated on unique populations of active duty firefighters and criminal scene-investigators (CSI) police, who are frequently exposed to similar levels and types of traumatic events, and compared them to civilian matched-controls with no history of trauma-exposure. We used a hippocampal dependent cue-context reversal paradigm, which separately evaluates reversal of negative and positive outcomes of cue and context related information. We predicted and found that all participants were equally able to acquire and retain stimulus-outcome associations. However, there were significant differences in reversal learning between the groups. Performance among firefighters replicated our prior findings; they struggled to learn that a previously negative context is later associated with a positive outcome. CSI police on the other hand showed a selective impairment in reversing the outcome of a negative cue. Hence after learning that a specific cue is associated with a negative outcome, they could not learn that later it is associated with a positive outcome. Performance in both groups did not correlate with levels of PTSD, anxiety, depression or behavioral inhibition symptoms. The results provide further evidence of the hidden price of traumatic exposure, suggesting that this price may differ as a function of occupation.